Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper analyzes the sources of the persistence of geographical unemployment imbalances and low speed of adjustment to regional labor demand shocks in Spain. The paper argues that, under present labor market arrangements, these imbalances are unlikely to be corrected in the near future. In particular, the current wage bargaining system appears to be excessively centralized and to result in nationally set wages that are too high to reduce unemployment in high-unemployment areas. The paper also analyzes the May 1997 labor market reform.